Saturday, August 6, 2016

Value propogation in verb and adjective narratives

We have relations like
A -v-> B
A _v/ B
The question is: how do the values associated to A, v, and B become a value for the whole expression? Let 0=bad and 1=good, we can write rules like the following.
Always ignore the value of A and use:
value( A -v-> B ) = value(B) + value(v) +1
value( A _v/ B ) = value(A)*value(B)
For fun you can write:
1 - val( A-v->B) = val(A) + val(B)
     val( A _v/ B ) =val(A) * val(B)
Also, it think we should use:
val( A, B) = val(B) 

No comments:

Post a Comment